2010
DOI: 10.5338/kjea.2010.29.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Various Heavy Metals on the Growth and Phosphorus (P) Removal Capacity of the Phosphorus Accumulating Microorganism (Pseudomonas sp.)

Abstract: The removal of phosphorus (P) in the wastewater is essential for the prevention of eutrophication in the river and stream. This study was initiated to evaluate the effect of the various heavy metals on the growth and P removal capacity of Pseudomonas sp., which was well known as phosphorus accumulating microorganism(PAO's) in the EBPR(Enhanced Biological Phosphorus Removal) process. The five heavy metals used in the study were Cu, As, Zn, Ni, and Cd. The growth rate of Pseudomonas sp. was the greatest at 25℃, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It was reported in the previous studies that these bacteria can be used in the biological P treatment and showed the high P removal efficiencies under the best optimal conditions (Kim et al, 2010;Yoo et al, 2011;Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in the previous studies that these bacteria can be used in the biological P treatment and showed the high P removal efficiencies under the best optimal conditions (Kim et al, 2010;Yoo et al, 2011;Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous studies, PAOs are sensitive to many factors including fluctuation of substrate concentration, inhibition from NO2 - (Saito et al, 2004), FNA (Zhou et al, 2010), metal ions (Kim et al, 2010, Tsai et al, 2016, dissolved oxygen, pH and temperature change (Lopez-Vazquez et al, 2009). Besides these, a well-known competitor of PAO, GAO, which also consumed carbon as PAO but does not contribute to phosphorous removal is blamed primarily for the deterioration of EBPR process (Gebremariam et al, 2011).…”
Section: Enhanced Biological Phosphorous Removal (Ebpr)mentioning
confidence: 99%